2009
DOI: 10.1002/chem.200802329
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐Coated Silver Nanoparticles: Synthesis, Surface Chemistry, and pH‐Triggered, Reversible Assembly into Particle Assemblies

Abstract: Simple tripeptides are scaffolds for the synthesis and further assembly of peptide/silver nanoparticle composites. Herein, we further explore peptide-controlled silver nanoparticle assembly processes. Silver nanoparticles with a pH-responsive peptide coating have been synthesized by using a one-step precipitation/coating route. The nature of the peptide/silver interaction and the effect of the peptide on the formation of the silver particles have been studied via UV/Vis, X-ray photoelectron, and surface-enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(112 citation statements)
references
References 97 publications
4
107
0
1
Order By: Relevance
“…Both techniques clearly show that the nanoparticles can be dispersed as single, stable entities and that they do not coalesce to larger objects once being in solution. In addition we have shown that our SNP remain stable from pH 3-10 ( Graf et al 2009). Out of this range, they start to precipitate and thus become instable, which might be related to instability of peptides at extreme pH values (Smith and Hansen 1998).…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 91%
See 2 more Smart Citations
“…Both techniques clearly show that the nanoparticles can be dispersed as single, stable entities and that they do not coalesce to larger objects once being in solution. In addition we have shown that our SNP remain stable from pH 3-10 ( Graf et al 2009). Out of this range, they start to precipitate and thus become instable, which might be related to instability of peptides at extreme pH values (Smith and Hansen 1998).…”
Section: Characterization Of Nanoparticlesmentioning
confidence: 91%
“…1. Nanoparticles were prepared according to an in-house protocol and characterized as published (Graf et al 2009). The nanoparticles became available in two diameter sizes, that is, 20 nm (Ag20Pep) and 40 nm (Ag40Pep), respectively.…”
Section: Nanoparticle Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the eVects of silver nanoparticles on human intestinal cells, we used peptide-coated silver nanoparticles with deWned colloidal, structural and interfacial properties (Graf et al 2009) and proliferating and diVerentiated Caco-2 cells. The nanoparticles consist of a 20 and 40 nm silver core coated with the small peptide L-cysteine L-lysine L-lysine.…”
Section: Introductionmentioning
confidence: 99%
“…The particles were synthesized and characterized as published by Graf et al [4] Concentration ranges of the SNPs were chosen with respect to dose-dependent impairment of phagocytosis of the macrophages as can be seen in. [3] THP-1 cells were differentiated into human macrophages during a period of 24 h. Afterwards, they were exposed to SNPs.…”
Section: Sample Preparationmentioning
confidence: 99%